Dynamic Resource Allocation based on priority approach in MIMO Cognitive Radio Networks – A Literature Surve - Tamilarasan, S; Kumar, P (International Journal of Computer Sciences and Engineering, 2025)
Cognitive radio networks (CRNs) are presently gaining massive recognition as the most-likely next-generation wireless communication paradigm. Naturally it has characteristic like attractive aptitude of modifying insufficient spectrum usage and/or underutilisation challenge. CRN is an excellent intellectual wireless radio communication system and it has great awareness of its environment. Here, heterogeneous hops spectrum sensing is great problem by means of fluctuating computing energy, range of sensing, and distribution of spectrum dynamically in CRN where there exist multiple primary users and secondary users have been considered. The scheduling of dynamic spectrum access methods provides a lot of challenges. Due to its demand many researchers were developed different system for spectrum allocation in dynamic fashion. The secondary users (SUs) likely exploit the spectrum when primary user’s absences, this technique would be improved the spectrum usage effectively. In this article we studied the different techniques were used to improve the spectrum usages and present the comprehensive analysis and comparison of each method which are used to improve the effective utilization of unused spectrum in CRN.